Cat Kid comic club - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Cat Kid Comic Club (Series), 2020)
Cat Kid creates a comic club with tadpole Molly and her twenty-one baby-frogs siblings as members to teach them how to make comics. They encourage the members to be unafraid to make mistakes and write the comics that they want to write.